Pendidikan Kesehatan dengan Pendekatan Model Information Motivation Behavior Skill (IMB) terhadap Peningkatan Pengetahuan dan Pola Konsumsi Sayur dan Buah pada Ibu Hamil - Farhati Farhati; Riska Resmana; Dian Nurhadianti (Jurnal Kesehatan, 2019)
Low consumption of vegetables and fruit causes an increased risk of chronic diseases such as cancer, heart disease, and diabetes. The results showed that the majority of pregnant women (52.9%) rarely consume vegetables and fruit in sufficient quantities as recommended. Therefore, it is necessary to provide education about the importance of vegetables and fruits consumption, one of which is through the Information Motivation Behavioral Skill (IMB) approach. This study aims to determine the effect of health education with the Information Motivation Behavior Skill (IMB) approach to increasing knowledge and consumption patterns of vegetables and fruits in pregnant women. This research is a quasi-experimental study with pre-post test design with control groups conducted in pregnant women in the city of Bandung with 60 samples using the observation sheet and questionnaire instruments. Data analysis used the chi-square test. The result of this study indicates that there are significant differences in knowledge and patterns of consumption of vegetables and fruit in pregnant women between the control and treatment groups with a p-value<0.05. Information Motivation Behavior Skill (IMB) Health Education Model approach has a role in increasing the knowledge and consumption patterns of vegetables and fruits in pregnant women.